Case Report: A Case Study Significance of the Reflective Parenting for the Child Development - Kostova, Zlatomira (Frontiers in Psychology, 2021)
There are studies that connect the „child“ in the past with the „parent“ in the present through the prism of high levels of stress, guilt, anxiety. This raises the question of the experiences and internal work patterns formed in childhood and developed through parenthood at a later stage. The article (case study) presents the quality of parental capacity of a family raising a child with an autism spectrum. The abilities of both parents to recognize and differentiate the mental states of their nonverbal child are discussed. An analysis of the parental representations for the child and the parent-child relationship is developed. The parameters of reflexive parenting are measured.